2010
DOI: 10.2478/s11756-010-0087-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sun irradiance and water availability on lichen photosynthetic pigments during a Mediterranean summer

Abstract: This study was carried out to investigate changes in lichen photosynthetic pigments induced by different combinations of light irradiance and water availability during a Mediterranean summer. To this purpose, thalli of three epiphytic lichens with a markedly different ecology concerning photo-hygrophytism, namely Evernia prunastri (hygro-mesophytic), Flavoparmelia caperata (mesophytic) and Xanthoria parietina (xero-mesophytic), were transplanted for 30 days to N-and S-facing cardinal exposures in central Italy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…caperata and later, after eight weeks in X. parietina) is perfectly in line with the autoecology of these species: F. caperata is mesophytic and potentially sensitive to extreme radiations under stressing microclimatic conditions, such as during a Mediterranean summer, while X. parietina is rather xerophytic and can better tolerate extreme conditions (Paoli et al, 2010b). Concerning the mycobiont, the investigated parameters suggested that oxidative stresses occurred in F. caperata and have been prevented in X. parietina.…”
Section: Discussionsupporting
confidence: 75%
“…caperata and later, after eight weeks in X. parietina) is perfectly in line with the autoecology of these species: F. caperata is mesophytic and potentially sensitive to extreme radiations under stressing microclimatic conditions, such as during a Mediterranean summer, while X. parietina is rather xerophytic and can better tolerate extreme conditions (Paoli et al, 2010b). Concerning the mycobiont, the investigated parameters suggested that oxidative stresses occurred in F. caperata and have been prevented in X. parietina.…”
Section: Discussionsupporting
confidence: 75%
“…Also previous studies indicated that Chl b is more sensitive than Chl a to high temperatures (Pisani et al 2007). Furthermore, the decrease in Chl b occurred earlier in E. prunastri (July) and only one month later (August) in P. furfuracea, suggesting a larger susceptibility of E. prunastri, probably caused by a limited ability of this species to maintain an active hydrated state (Paoli et al 2010). On the other side, no clear trend of Chl a/b was detected along the altitudinal gradient.…”
Section: Assimilation Pigmentsmentioning
confidence: 71%
“…In the same area, significant correlations were found between the content of Cu, Pb and Zn in the lichen Usnea amblyoclada exposed around the cement mill and the content of hydroperoxy conjugated dienes, suggesting an important oxidative effect caused by these ions (Carreras and Pignata 2002). In addition to dust pollution, microclimatic parameters may influence physiological processes of lichens, in particular during the dry season, when sun irradiance and water availability may heavily affect chlorophyll fluorescence emission and the content of photosynthetic pigments (Paoli et al 2010;Pirintsos et al 2011). Also, the type of deposition can vary according to humidity and precipitation.…”
Section: Physiological Effectsmentioning
confidence: 96%